Robótica e educação: uma possibilidade de inserção sócio-digital - Silva, Akynara Aglae Rodrigues Santos da (2010)
This paper presents a reflection on the use of robotics in education technology and the fostering of social and digital inclusion, unveiling a new field that has been outlined today. Robotics constitutes a tool still little known and not regulated at national level in education, there is little experience involving the tool in the Northeast. This research aims to reveal one of the first experiments with educational level robotics in Rio Grande do Norte. We present a field research conducted in a public school chancellor for a major institute of science and technology education of the state from seeking review of the robotics course, understand how they work and show their use in school and shows that contributions were generated for digital inclusion category students, based on speeches by teachers, engineers, management and students. As part of gathering information, we used the focus group technique, applied in two stages, one with groups of students, teachers and other school administration, as well as comments directed to the times when the robotics course was being finalized. As a result, we found that the school, through the robotics course is a provider of social and digital inclusion, since it awakens in the sample of students in this research knowledge enabler of social change. And that despite the student category do not understand the depth of meaning of inclusion, the same report in daily actions that integrate technology into their social context in harmony, enjoying its cultural citizenship in full